S = 1 ⋅ 2 1 + 2 ⋅ 3 2 + 3 ⋅ 4 3 + 4 ⋅ 5 4 + 5 ⋅ 6 0 + 6 ⋅ 7 1 + . . . = k = 1 ∑ ∞ k ( k + 1 ) k mod 5
Evaluate the infinite sum above and enter ⌊ 1 0 1 0 S ⌋ .
Notation : ⌊ ⋅ ⌋ denotes the floor function.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
( 1 1 + 2 1 + 3 1 + . . . ) − 5 ( 5 1 + 1 0 1 + 1 5 1 + . . , ) = ∞ − ∞
Log in to reply
I have done the changes.
Log in to reply
n → ∞ lim ( 1 1 + 2 1 + 3 1 + . . . + 5 n 1 ) − n → ∞ lim 5 ( 5 1 + 1 0 1 + 1 5 1 + . . . + 5 n 1 ) = ∞ − ∞
Log in to reply
@Pi Han Goh – The mechanics aren't rigorous ( there shouldn't be an "n" remaining after a limit is taken, and it doesn't make sense to say that lim n → ∞ H n = l n ( n ) − γ ) but his general idea is correct (and quite creative!).
If we call S n = ∑ k = 1 n k ⋅ ( k + 1 ) k mod 5 , then through Chew-Seong Cheong's methods from the first three lines, we can see that the following holds:
S 5 = 1 1 + 2 1 + 3 1 + 4 1 + 5 1 − 5 5
S 1 0 = 1 1 + 2 1 + 3 1 + 4 1 + 5 1 − 5 5 + 6 1 + 7 1 + 8 1 + 9 1 + 1 0 1 − 1 0 5
= ( 1 1 + 2 1 + 3 1 + 4 1 + 5 1 + 6 1 + 7 1 + 8 1 + 9 1 + 1 0 1 ) − ( 1 1 + 2 1 )
As long as the index is a multiple of 5, the above structure holds. So we guarantee that by defining T n = S 5 n ; i.e.
T n = ( 1 1 + 2 1 + 3 1 + . . . + 5 n 1 ) − ( 1 1 + 2 1 + . . . + n 1 )
So,
= [ 1 1 + 2 1 + 3 1 + . . . + 5 n 1 − l n ( 5 n ) ] − [ 1 1 + 2 1 + . . . + n 1 − l n ( n ) ] + l n ( 5 n ) − l n ( n )
= [ 1 1 + 2 1 + 3 1 + . . . + 5 n 1 − l n ( 5 n ) ] − [ 1 1 + 2 1 + . . . + n 1 − l n ( n ) ] + l n ( 5 )
As n → ∞ , then 5 n → ∞ , so the first portion of T n goes to γ , as does the second portion. Since both exist, we can subtract one limit from the other:
lim n → ∞ S n = lim n → ∞ T n = γ − γ + l n ( 5 ) = l n ( 5 )
Ah, I follow it now. Excellent. My proof is completely different.
Problem Loading...
Note Loading...
Set Loading...
S = n → ∞ lim ( 1 ⋅ 2 1 + 2 ⋅ 3 2 + 3 ⋅ 4 3 + 4 ⋅ 5 4 + 5 ⋅ 6 0 + 6 ⋅ 7 1 + . . . + ( 5 n − 1 ) ⋅ 5 n 4 + 5 n ⋅ ( 5 n + 1 ) 0 ) = n → ∞ lim ( 1 1 − 2 1 + 2 2 − 3 2 + 3 3 − 4 3 + 4 4 − 5 4 + 0 + 6 1 − 7 1 + . . . + 5 n − 1 4 − 5 n 4 + 0 ) = n → ∞ lim ( 1 1 + 2 1 + 3 1 + 4 1 + 5 1 − 5 5 + 6 1 + 7 1 + . . . + 5 n − 1 4 + 5 n 1 − 5 n 5 ) = n → ∞ lim [ ( 1 1 + 2 1 + 3 1 + . . . + 5 n 1 ) − 5 ( 5 1 + 1 0 1 + 1 5 1 + . . . + 5 n 1 ) ] = n → ∞ lim [ ( 1 1 + 2 1 + 3 1 + . . . + 5 n 1 ) − ( 1 1 + 2 1 + 3 1 + . . . + n 1 ) ] = n → ∞ lim ( H 5 n − H n ) = ln ( 5 n ) + γ − ln ( n ) − γ = ln 5 See note below.
Note : n → ∞ lim H n = ln ( n ) − γ , where H n is the n th harmonic number and γ is the Euler-Mascheroni constant .